Trends in the prevalence of infiltrative cardiomyopathy among patients with in-hospital cardiac arrest – insight from the US national inpatient sample database. (3rd October 2022) - Nandy, S; Hajra, A; Malik, A; Bandyopadhyay, D; Abou-Ezzeddine, O; Grogan, M; Mankad, R; Klarich, K W
Abstract: Background: Sarcoidosis, amyloidosis, hemochromatosis and scleroderma are the most common systemic disorders leading to infiltrative cardiomyopathy (InCM). Each of them has been associated with conduction abnormalities and sudden cardiac death. In patients who undergo in-hospital cardiac arrest, a high index of suspicion is required to rule out InCM as an underlying contributor. Purpose: We aimed to analyse the temporal trend in the prevalence of InCM among patients with in-hospital cardiac arrest and identify factors associated with increased mortality in this population. Methods: We analysed data from the National Inpatient Sample (NIS), which is the largest publicly available database of in-hospital patients in the Unites States. Using ICD-10 coding, we identified patients who were hospitalized across 10 years from 2010–2019. Patients with diagnosis codes for both cardiac arrest and a subtype of InCM were included. Demographic characteristics and co-morbidity data were collected. Statistical analysis was performed using STATA. Results: The total number of patients with a diagnosis of in-hospital cardiac arrest was 19, 34, 260. Of these, the total number with InCM was 14, 803 (0.77%), which comprised our study population. Mean age was 63 years. The overall prevalence of InCM across the years ranged between 0.75 to 0.9%, with a significant temporal increase (p<0.01). Prevalence of females ranged between 51% to 62% and significantly outnumbered males across the time period. (p=0.011). Incidence of in-hospital mortality ranged between 61% to 76% for females and 30 to 38% for males. Race based analysis showed that prevalence of Caucasians ranged from 51% to 62% while that of African Americans (AA) ranged from 57% to 73%. The incidence of mortality was similar in both populations. Sarcoidosis was the most prevalent form of InCM, accounting for nearly two-fifths of all cases while amyloidosis and scleroderma both accounted for nearly 20% each. Haemochromatosis was present in 10% of the population. Overall mortality rate in our study population was 60.6%. The following co-morbidities were more prevalent in patients with InCM than those without: history of heart failure, chronic obstructive pulmonary disease (COPD), chronic kidney disease, anaemia, malignancy, coagulopathy, ventricular tachycardia, acute kidney injury and stroke. The following factors were independent predictors of in-hospital mortality-age (p=0.001), female gender (p=0.016), Hispanic race (p=0.039), history of COPD (p<0.001) and presence of malignancy (p=0.042). Conclusion: The prevalence of infiltrative cardiomyopathy in patients with in-hospital cardiac arrest is increasing. Females, older patients and Hispanic population are at an increased risk of mortality. Sex and race based disparities in the prevalence of InCM in patients with in-hospital cardiac arrest is an area of further research. Funding Acknowledgement: Type of funding sources: None.